2020
DOI: 10.1002/star.202000206
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Effects of Xanthan Gum at Different Concentrations on the Functional, Thermal, and Digestibility Characteristics of Corn and Sorghum Starch Extrudates

Abstract: The present study assesses the concentration dependent effect of xanthan gum, that is, 0%, 0.5%, 1%, and 2% (w/w), at 50% feed moisture, on the in vitro digestibility of corn and sorghum starch extrudates. Sorghum starch, being extracted from an underutilized and drought‐resistant crop, provides a promising alternative to corn starch in the future. X‐ray and Fourier transform infrared (FTIR) results show that xanthan gum at 1% has optimum synergistic interaction with corn and sorghum extrudates. The percent cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…All the same, Shaikh et al. [ 35 ] concluded that retrograded corn starch powders exhibited lower paste viscosity as compared to its normal corn starch powders in concentrated solution of (40%), too. It was attributed to the amylose that had leached out of starch granules and would have restricted the water‐uptake and swelling of the dry powders.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…All the same, Shaikh et al. [ 35 ] concluded that retrograded corn starch powders exhibited lower paste viscosity as compared to its normal corn starch powders in concentrated solution of (40%), too. It was attributed to the amylose that had leached out of starch granules and would have restricted the water‐uptake and swelling of the dry powders.…”
Section: Resultsmentioning
confidence: 97%
“…The flow characteristics of mayonnaise samples were determined following the method of Gaur et al. [ 16 ] Initially, shear rate was increased from 0.1 to 200 s −1 (up‐curve) followed by decrease in shear rate from 200 to 0.1 s −1 (down curve). The shear stress was measured as a function of shear rate for both up and down curves.…”
Section: Methodsmentioning
confidence: 99%